Case report of an uncommon case of drain-site hernia after colorectal surgery. (2018) - Manigrasso, M.; Anoldo, P.; Milone, F.; De Palma, G.D.; Milone, M.
Highlights: Trocar site herniation is a rare but potentially serious complication of laparoscopic surgery. We report an uncommon case of drain site hernia. The risk of trocar site hernia in laparoscopy has been known since 1967. Other two cases are described in literature regarding pediatric and gynaecologic patients. Drain should not be positioned through the 10 mm trocar in order to avoid any herniation. Abstract: Background: trocar site herniation is a rare but potentially serious complication of laparoscopic surgery. Data about drain site hernia after laparoscopic surgery is scarce and anecdotal. Case presentation: we report an uncommon case of drain site hernia in a man undergone laparoscopic left colectomy for a colonic adenocarcinoma who developed small bowel herniation in a 10 mm port site, in which a 24 FR drain was inserted leaving a real free space of 2 mm. Discussion: laparoscopic approach has gained widespread acceptance in each surgical fields because of the perceived better postoperative outcomes in terms of less pain, faster recovery, and lower risk of incisional hernia. However, the risk of trocar site hernia has been known since 1967. Different risk factors for the development of trocar site hernia are described in literature: the trocar diameter and design, preexisting fascial defects, enlargement of a port site to remove a specimen, high blood glucose levels, obesity, increase intra-abdominal pressure as in chronic obstructive airway disease or extensive manipulation of the trocar during surgical intervention, which may enlarge the trocar site and thus induce small bowel herniation. However, the most important recognized risk factor for trocar site hernia is the size of the trocar. Conclusions: waiting for further studies, the lesson to be learnt from this case report is that, even if the free space after drain positioning is minimal, drain should not be positioned through the 10 mm trocar to allow the closure of fascial defect in order to avoid any herniation.